Marginal Effects of Factors Influencing Procurement Records Management: A Survey of Selected Procuring Entities in Tanzania - Mohamed, Bakari Maligwa; Rasheli, Geraldine Arbogast; Mwagike, Leonada Rafael (International Journal of Social and Administrative Sciences, 2018)
This paper estimated marginal effects on dependent variable against independent variables on the management of procurement records in the Tanzania procuring entities (PEs). The study was a survey of selected PEs. Data were collected through structured questionnaires. Sample was arbitrarily set at 200 PEs whereby questionnaires were randomly administered to 200 respondents within 200 PEs found in Dar es Salaam, Dodoma, Morogoro, Pwani, and Tanga. At the end of questionnaires administration the response rates were 83.1% PEs and 75% respondents respectively. Based on the results and findings, marginal effects were identified, established and estimated. The study was concluded that: PEs having no equipment and facilities for keeping records are 2.7% less likely to have proper management of procurement records, PEs with limited equipment and facilities for keeping records are 4.1% less likely to have proper management of procurement records, and PEs with no security and safety measures in managing records are 1.4% less likely to have proper management of procurement records, ceteris paribus. On the contrary, procurement records managed by personnel who are knowledgeable and skilled are 1.3% more likely to be properly managed, procurement records that are managed by competent personnel and who have the on-the-job training on records management are 1.0% more likely to be properly managed, PEs with available storage space for keeping records, improves management of procurement records by 4.8%, PEs with adequate storage space for keeping all kinds of procurement records, improves management of procurement records by 6.5%, and PEs that have sufficient security and safety measures in managing procurement records, improves management of procurement records by 4.3% ceteris paribus.